2019
DOI: 10.1186/s12913-019-4402-9
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge, ability, and skills of primary health care providers in SEANERN countries: a multi-national cross-sectional study

Abstract: Background Primary health care (PHC) is usually the initial point of contact for individuals seeking to access health care and providers of PHC play a crucial role in the healthcare model. However, few studies have assessed the knowledge, ability, and skills (capacity) of PHC providers in delivering care. This study aimed to identify the capacity of PHC providers in countries of the Southeast and East Asian Nursing Education and Research Network (SEANERN). Methods A mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…30,202 A reliable PHC system that provides the first line point of healthcare to communities, drawing together knowledge, skills, and resources through inter-sectoral collaboration helps in the early detection, prevention, and control of NCDs. 203 At an individual patient level, PHC systems record their longitudinal personal and medical history, which helps in the understanding of the disease development process, especially for long term conditions. 204,205 A PHC approach can also identify and address the community health needs of various population groups and respond to geographical differences through acceptable, affordable, and accessible prevention and control measures.…”
Section: Discussionmentioning
confidence: 99%
“…30,202 A reliable PHC system that provides the first line point of healthcare to communities, drawing together knowledge, skills, and resources through inter-sectoral collaboration helps in the early detection, prevention, and control of NCDs. 203 At an individual patient level, PHC systems record their longitudinal personal and medical history, which helps in the understanding of the disease development process, especially for long term conditions. 204,205 A PHC approach can also identify and address the community health needs of various population groups and respond to geographical differences through acceptable, affordable, and accessible prevention and control measures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to health workforce shortages, several papers report on workforce training gaps ( Du et al. , 2019 ; Fadlallah et al.…”
Section: Resultsmentioning
confidence: 99%
“…, 2014 ). One study found a widespread lack of skills, confidence and adequate training among primary care nurses in Southeast and East Asian countries in areas such as safe water and sanitation, nutritional promotion, endemic diseases prevention and essential drugs, which inhibit their ability to assess and manage patients’ needs, demonstrating an urgent need for enhanced provider training ( Du et al. , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many nurses have a strong sense of professional obligation to provide nursing care during a pandemic. However, the uncertainty of the situation, extreme pressures of high workload demands and need to prioritize resources have been reported to create feelings of vulnerability, loneliness, powerlessness, and both physical and psychological exhaustion [27]. The impact of the nursing role is also overlaid with the psychological impacts facing all members of the community in terms of fear of contracting the pathogen, concerns for family and the impacts of social isolation [28].…”
Section: Impact Of Covid-19 On Nursing Care Processes and Care Deliverymentioning
confidence: 99%